(untitled) (Canadian Eye Care Today, 2022)
More and more patients are consulting the internet for medical information following a diagnosis or before consenting to medical or surgical treatment. A quick Google search for “What happens if I get diagnosed with glaucoma”, reveals some very discouraging information, including “glaucoma can lead to blindness”. Many people will not read further to better understand that, with appropriate treatment and follow-up, they can preserve good functional vision for life. Instead, they focus on the potential negative outcomes such as job loss, loss of independence and a vastly reduced quality of life. It is important to remember that “a patient’s assessment of his or her objective situation can differ significantly from a physician’s assessment and prognosis.” At the time of diagnosis, patients need to know and hear the “good news”, such as the treatments that are available and the backup options in case of treatment failure. Explaining the treatment strategy can help prevent or ease anxiety. Managing expectations can help build trust between the patient and the doctor and provides the patient confidence in the treatment plan.